2021
DOI: 10.3390/medicina57111207
|View full text |Cite
|
Sign up to set email alerts
|

Angular Heterotopic Pregnancy: Successful Differential Diagnosis, Expectant Management and Postpartum Care

Abstract: Heterotopic pregnancy is a rare, difficult to diagnose and life-threatening pathology, which requires timely decisions made by an experienced multidisciplinary team. In this type of multiple pregnancy there are both intrauterine and ectopic pregnancies present. Its incidence increases in pregnancies conceived by assisted reproductive technology or in pregnancies with ovulation induction. This article presents an angular heterotopic pregnancy case in a 34-year-old multigravida. The patient was admitted on the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A HP is a rare, difficult-to-diagnose, and life-threatening pathological condition [7][8][9] that occurs mostly in women conceived using ART such as in vitro fertilization, ovulation induction, and intrauterine insemination. 10,11 The incidence has been reported to be as high as 1:100 in ART-conceived pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…A HP is a rare, difficult-to-diagnose, and life-threatening pathological condition [7][8][9] that occurs mostly in women conceived using ART such as in vitro fertilization, ovulation induction, and intrauterine insemination. 10,11 The incidence has been reported to be as high as 1:100 in ART-conceived pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Our study showed that the average pregnancy loss rate for HP within 2 weeks of surgery was 12.3% (13/106), which was similar to the 12% to 17% miscarriage rate reported in previous studies. [1,11,13,21,22] Moreover, considering that spontaneous abortion occurs in 11% to 65% of viable IUPs, surgical intervention for HP is considered safe and does not augment the risk factors for miscarriage of viable IUPs in patients with HP. [23] Our study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of serum human chorionic gonadotropin (hCG) in these patients can lead to atypical clinical symptoms. 4 Thus, early diagnosis and early treatment are challenging in these patients. We herein report a case involving a woman with an intrauterine hydatidiform mole and tubal pregnancy who was admitted to our hospital.…”
Section: Introductionmentioning
confidence: 99%